Evaluation of the relationship between c-Kit expression and mean platelet volume in classic Kaposi's sarcoma - Ibrahim Sehitoglu; Recep Bedir; Erkan Cure; Medine Cumhur Cure; Suleyman Yuce; Nursel Dilek (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: c-Kit is a proto-oncogene that encodes tyrosine kinase receptor (CD117). Mean platelet volume (MPV) is a useful marker, providing information on platelet function and diameter. Objective: To investigate c-Kit expression and intensity in patients with Kaposi's sarcoma (KS) and to investigate the relation between Ki-67 proliferation and MPV. Methods: A total of 32 patients, diagnosed with classic cutaneous KS, were included in this study. We reevaluated the histopathological reports with the preparations, confirmed the diagnosis and then determined the patients' histopathological stages. c-Kit expression and Ki-67 proliferation were investigated immunohistochemically in KS cases, while MPV in all cases was checked. Results: Although c-Kit expression was detected in 22 cases (68.8%), it was not expressed in 10 cases (31.2%). We detected 8 cases with + (25%), 6 with ++ (18.8%) and 8 with +++ (25%). Ki-67 expression was 5.0% (min-max 1.0-20.0). Relapse was observed in 5 cases (15.6%) out of 32. There was positive correlation between c-Kit expression and MPV (rs=0.598, p<0.001), and between c-Kit intensity and MPV (rs=0.588, p<0.001). Conclusion: c-Kit is highly positive in KS. c-Kit positivity indicates a high risk of tumor growth, invasion and relapse. Furthermore, c-Kit expression stimulates megakaryocytes to release young and large thrombocytes into the periphery. Thus, high MPV, c-Kit expression and immunostaining intensity indicate high invasion and relapse in KS subjects.